2019
DOI: 10.1177/0886260519872985
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Sexual Violence and Mental Health Indicators Among Chinese Emerging Adults

Abstract: Intimate partner sexual violence (IPSV) among emerging adults, including heterosexuals and sexual minorities in the Chinese population, is poorly understood. Focusing on college students, the objectives of the present study were to estimate the prevalence of IPSV among Chinese emerging adults, examine the association between sexual orientation and IPSV, and evaluate the mental health and quality of life of survivors of IPSV. Data were collected from four university campuses in Hong Kong. A total of 1,015 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…Consistent with findings of various previous studies [2][3][4][5][10][11][12], this study found among men and women that physical IPV and/or sexual violence victimization was associated with sexual risk behaviour (having had multiple sexual partners, alcohol use in the context of sex, diagnosed with HIV and pregnancy), and violence related behaviour (been in a physical fight and carried a weapon). In agreement with previous findings [2,5,6,[8][9][10][11][12][13][16][17][18][19][20], physical IPV and/or sexual violence victimization was overall and among women associated with all 5 mental health indicators (depression, loneliness, PTSD, sleeping problem and short sleep) and among men 2 poor mental health indicators (PTSD and sleeping problem), and overall victimization was associated with 3 addictive behaviours (alcohol, tobacco and drug use), among women 2 addictive behaviours (binge drinking and tobacco use) and among men 2 addictive behaviours (tobacco use and drug use).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with findings of various previous studies [2][3][4][5][10][11][12], this study found among men and women that physical IPV and/or sexual violence victimization was associated with sexual risk behaviour (having had multiple sexual partners, alcohol use in the context of sex, diagnosed with HIV and pregnancy), and violence related behaviour (been in a physical fight and carried a weapon). In agreement with previous findings [2,5,6,[8][9][10][11][12][13][16][17][18][19][20], physical IPV and/or sexual violence victimization was overall and among women associated with all 5 mental health indicators (depression, loneliness, PTSD, sleeping problem and short sleep) and among men 2 poor mental health indicators (PTSD and sleeping problem), and overall victimization was associated with 3 addictive behaviours (alcohol, tobacco and drug use), among women 2 addictive behaviours (binge drinking and tobacco use) and among men 2 addictive behaviours (tobacco use and drug use).…”
Section: Discussionsupporting
confidence: 93%
“…The study also found some evidence that physical IPV and/or sexual violence victimization was associated other health risk behaviours, such as an unhealthy diet (skipping breakfast and frequent salt intake), as found in a previous study [15]. Contrary to some previous investigations [5,15,[19][20][21][22][23], this study did not find an association between physical IPV and/or sexual violence victimization and physical inactivity, inadequate fruit and vegetable intake, not always wearing a seatbelt, poor self-rated health status, and poorer educational outcomes. In addition, some studies found an association between physical IPV and injury [5,10], while this study did not find this association.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The International Dating Violence Study, which was conducted with college students in 32 countries, revealed that 30% of students had experienced physical assault and 20% had experienced sexual coercion over the past year (Straus, 2008). Recent statistics gathered in Hong Kong reported that a lower but substantial proportion of students in Hong Kong experience dating violence, with prevalence rates of 16.6% for physical victimization and 12.1% for sexual coercion among college students (Wong et al, 2019). Given the prevalence of physical and sexual violence among college students, effective programs for the prevention of dating violence are increasingly important.…”
Section: Introductionmentioning
confidence: 99%